Addressing the "Global Health Tax" and "Wild Cards": Practical Challenges to Building Academic Careers in Global Health. (January 2016) - Palazuelos, Daniel; Dhillon, Ranu
Abstract : Among many possible benefits, global health efforts can expand the skills and experience of U.S. clinicians, improve health for communities in need, and generate innovations in care delivery with relevance everywhere. Yet, despite high rates of interest among students and medical trainees to include global health opportunities in their training, there is still no clear understanding of how this interest will translate into viable and sustained global health careers after graduation. Building on a growing conversation about how to support careers in academic global health, this Perspective describes the practical challenges faced by physicians pursuing these careers after they complete training. Writing from their perspective as junior faculty at one U.S. academic health center with a dedicated focus on global health training, the authors describe a number of practical issues they have found to be critical both for their own career development and for the advice they provide their mentees. With a particular emphasis on the financial, personal, professional, and logistical challenges that young "expat" global health physicians in academic institutions face, they underscore the importance of finding ways to support these career paths, and propose possible solutions. Such investments would not only respond to the rational and moral imperatives of global health work and advance the mission of improving human health but also help to fully leverage the potential of what is already an unprecedented movement within academic medicine.